Business ethics, illegal trade practices and rise of e-commerce industry - Lina Maulidiana, Idham, Tulus Suryanto, (Opción, 2019)
This study examined the new laws related to online business in Indonesia and the extent of freedom given to foreign investors. It also discusses whether new regulations would be able to check illegal trade practices. Using a survey methodology the study identified a few issues related to e-commerce transaction in Indonesia. Findings reveal that the Indonesian online business is growing but at the cost of compromises with legal mechanisms. In conclusion, the current study has assessed the need and importance of a legal mechanism to exist within the domestic Indonesian law to prevent unethical practices in ecommerce transactions.